Genetic aspects of birth defects: New understandings of old problems - Prescott, K; Wilkie, A (2007)
Over the past two decades, combined advances in genetics, developmental biology and biochemistry have transformed the study of human birth defects. This review describes the importance of genome architecture, parent of origin effects (imprinting), molecular pathophysiology, developmental pathways, mosaicism and cancer predisposition syndromes in the understanding of birth defects. This knowledge can be applied to improve diagnostic accuracy, prognostic information, counselling and sometimes even treatment of these conditions.